Analysis of the Effect of Delivery Service Quality on Customer Satisfaction of PT. JNE - Hanafi, Dedi; Harahap, Raja Sakti Putra (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2025)
This research aims to test whether there is an influence on the quality of service, on customer satisfaction toward PT. JNE Kota Binjai. The study used primary data with the dissemination of questionnaires. The population in the study is the general public of Jakarta who use jne express delivery service with a sample number of 100 respondents using purposive sampling technique. The data processing method in this search uses structural equation modeling (SEM) by using the SmartPLS 3.0 application. The results of this study show that service quality variables have a significant effect on customer satisfaction. Then variable pricing has no effect on customer satisfaction. Facility variables have no effect on customer satisfaction. Furthermore, the quality of service has a significant effect on trust. Then variable pricing has no effect on trust. Facility variables have a significant effect on trust. Furthermore, customer satisfaction variables directly have no effect on trust. So it can be said that customer satisfaction does not affect customer trust.